PERBEDAAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SESUDAH PENGUMUMAN RIGHT ISSUE DI BEI - S Wibawa, I Gede Andika; Suryantini, Ni Putu Santi (E-Jurnal Manajemen, 2019)
The right issue phenomenon that occurred in Indonesia in 2016 and 2017, there were 52 companies that experienced rights issues from all sectors of the company listed on the Indonesia Stock Exchange, with non-probability sampling method with saturated sampling techniques. The purpose of this study was to determine the market reaction in the event of a right issue as measured by abnormal returns, abnormal returns according to the grouping of company size data, and trading volume. Data collection is done by observing and recording data from reports and archives from several sources with data analysis techniques that are normality testing and hypothesis testing. Based on data analysis conducted in the study, it was found that partially the rights issue announcement did not have a significant impact on abnormal returns and abnormal returns according to the grouping of company size data. While the right issue announcement has a significant  negative effect on trading volume. This shows that there is a negative reaction from investors regarding the rights issue announcement by the company .